2020
DOI: 10.4018/978-1-7998-2577-7.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Capability for SME Biomass Industry Performance

Abstract: Industry 4.0 exerts great pressure on the organization today to innovate its business model in order to stay competitive. This study examines the positive and indirect effect of human resource management, organizational culture, knowledge management capabilities on organizational performance, with the mediating effect of organizational innovation capability among small and medium-sized enterprise (SME) in biomass industry in Malaysia. In addition, this study integrates resource-based view (RBV) and dynamic cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Their definition includes a range of innovation outcomes, such as new products, platforms and services as well as new customer experiences and other value lines, this is made possible as a result through the use of digital technologies and digital processes. In line with the opinion ofFang et al (2020);Haudi et al (2022) that digital innovation is the development of new products, services or solutions using digital technology. In addition, digital innovation is contextualized into innovative digital as a solution that can change products, services, and other organizational businesses.From the various definitions stated above, it can be concluded that innovationDigital is a technology made by companies based on the results of innovation in the form of creating new products that can be used as solutions to existing problems.Company PerformanceAccording toAbudaqa et al (2022);AlMulhim et al (2021) that company performance results from an evaluation of the implementation of company policies.…”
mentioning
confidence: 81%
“…Their definition includes a range of innovation outcomes, such as new products, platforms and services as well as new customer experiences and other value lines, this is made possible as a result through the use of digital technologies and digital processes. In line with the opinion ofFang et al (2020);Haudi et al (2022) that digital innovation is the development of new products, services or solutions using digital technology. In addition, digital innovation is contextualized into innovative digital as a solution that can change products, services, and other organizational businesses.From the various definitions stated above, it can be concluded that innovationDigital is a technology made by companies based on the results of innovation in the form of creating new products that can be used as solutions to existing problems.Company PerformanceAccording toAbudaqa et al (2022);AlMulhim et al (2021) that company performance results from an evaluation of the implementation of company policies.…”
mentioning
confidence: 81%
“…States SBA, the Malaysian SME corporation defines the SME based on its manufacturing and service industry (Fang et al, 2020). Unlike SBA, which defines manufacturing and mining based on employees, while annual nonmanufacturing is based on turnover, SMEs in each of the two industries in Malaysia are defined based on annual sales turnover and full-time employees (Fang et al, 2020). The manufacturing industry SMEs of Malaysia are firms employing not less than 200 full-time staff and having an annual sales turnover of not less than RM50 million (Fang et al, 2020).…”
Section: Defining Smementioning
confidence: 99%
“…Unlike SBA, which defines manufacturing and mining based on employees, while annual nonmanufacturing is based on turnover, SMEs in each of the two industries in Malaysia are defined based on annual sales turnover and full-time employees (Fang et al, 2020). The manufacturing industry SMEs of Malaysia are firms employing not less than 200 full-time staff and having an annual sales turnover of not less than RM50 million (Fang et al, 2020). The SME in Malaysia's service industry employs not less than 75 persons full-time and enjoys an annual turnover of not less than RM20 million (Fang et al, 2020).…”
Section: Defining Smementioning
confidence: 99%
“…According to Malaysia's Personal Data Protection Act, blockchain technology might threaten people's privacy intentionally or unintentionally especially when involving cross-border transactions [46]. Malaysia's trading companies may face serious challenges on how to handle trade data ownership especially trade finance data that might affect their competitive advantage.…”
Section: Challenges Of Blockchain Implementation In Land Registry Systemmentioning
confidence: 99%
“…It will be able to track such transactions and thus, tax collection will be affected. Continuous security monitoring is a prerequisite in this sphere, both for commercial and government deployment [46].…”
Section: Challenges Of Blockchain Implementation In Land Registry Systemmentioning
confidence: 99%